ANALISIS KEKUATAN MEKANIK WATER COOLING TANK PADA FASILITAS UJI UNTAI PASSIF-02 MENGGUNAKAN CATIA - Dedy Haryanto Haryanto (Jurnal Ilmiah Teknik Mesin POROS, 2018)
Strand Test Facility has been constructed and will be used for passive reactor core cooling simulation research without using a pump or outside force, so that the movement of water flow occurs naturally. One important component of the FASSIP-02 is the water cooling tank (WCT), in addition to piping, expansion tanks (ET) and water heating tanks (WHT). WCT containing water such as a pond that functions to take heat in the water from the FASSIP-02 piping system with a position at an altitude of 11 meters. The total load of water and tank is 10 tons and for safety and security factors during operation it is necessary to analyze the mechanical strength of the WCT. Analysis is done by simulating mechanical stress conditions and translational displacement to determine the safety of WCT when operating. The stages of analysis include making a 3-dimensional model equipped with the mechanical properties of the material used, giving a load on the 3-dimensional WCT model, giving restrain to simulate the stable condition of the 3-dimensional model and testing it in simulation. The results of the analysis show that the mechanical stress on the WCT is still in the elastic area of the Carbon Steel AISI 1040 material if the temperature of the secondary water in WCT is less than 90 ° C. The primary water operating temperature is a maximum of 90 ° C and the secondary water temperature does not reach 90 ° C due to heat transfer from primary to secondary. Translational displacement that occurs is very small when compared to the WCT dimension so that it does not result in a change in shape in the WCT. Thus the design of the WCT can be continued to be constructed and safely operated.